2002
DOI: 10.1046/j.1463-1326.2002.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of glycation, antioxidant status and oxidativestress to vascular endothelial damage in diabetes

Abstract: In diabetes, glycation, tissue oxidation and endothelial function are all abnormal and predisposing to microvascular complications but interrelationships are complex with glycation appearing most direct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 19 publications
(20 reference statements)
1
20
0
1
Order By: Relevance
“…Vascular NO is critical for normal vasodilatation and endothelial function, and impairment of NO bioavailability and the NO-cyclic guanosine monophosphate (cGMP)-cGMP-dependent protein kinases (PKG) signaling cascade can lead to endothelial dysfunction [3]. A number of clinical studies have shown that hyperglycemia and increased AGEs are key factors in potentiating vascular inflammation and increasing levels of reactive oxygen species (ROS) and oxidative stress [4], [5]. This vascular milieu of elevated inflammation, impaired NO bioavailability, and oxidative stress plays an integral role in the progression of atherosclerosis and subsequently acute coronary syndromes culminating in significant morbidity and mortality of the diabetic patient [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular NO is critical for normal vasodilatation and endothelial function, and impairment of NO bioavailability and the NO-cyclic guanosine monophosphate (cGMP)-cGMP-dependent protein kinases (PKG) signaling cascade can lead to endothelial dysfunction [3]. A number of clinical studies have shown that hyperglycemia and increased AGEs are key factors in potentiating vascular inflammation and increasing levels of reactive oxygen species (ROS) and oxidative stress [4], [5]. This vascular milieu of elevated inflammation, impaired NO bioavailability, and oxidative stress plays an integral role in the progression of atherosclerosis and subsequently acute coronary syndromes culminating in significant morbidity and mortality of the diabetic patient [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, eNOS knockout mice had decreased oxygen consumption, increased weight gain and were resistant to insulin [11]. In addition, several studies have indicated that insulin resistance itself may impair NO release and damage the endothelium through mechanisms that are reciprocally interconnected [4], [5]. For example, chronic hyperglycemia has been shown to increase circulating levels of inflammatory cytokines, chemokines, and expression of intracellular adhesion molecule-1, hence contributing further to this pathognomonic state [12].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic endothelial dysfunction is the result of imbalance between reactive oxygen species (ROS), increased via antioxidant and glycation pathways, and the production and availability of NO, that is reduced (5,6,7,8). In addition, an increase in serum levels of vasoconstrictors, such as endothelin 1 (ET1) (9), and an impairment of several hemodynamic parameters, such as flow-mediated dilation (FMD) at brachial artery, intima-media thickness, and blood pressure (10), were described.…”
mentioning
confidence: 99%
“…Adjustment for waist circumference instead of BMI or further adjustment for baseline levels of C-reactive protein, fasting insulin, and HbA1c or exclusion of cases diagnosed during the first 4 years of followup did not alter these associations (Meigs et al, 2004). In the other hand, in diabetes, glycation, tissue oxidation and endothelial function are all abnormal and predisposing to microvascular complications but interrelationships are complex with glycation appearing most direct (Wen et al, 2002). The patients with microalbuminuria, unlike those without it, are characterized by longer course of diabetes, more pronounced lipid exchange disorder, more variable arterial pressure, higher pressure load index, elevated activity of lipid peroxidation (LP) processes and prominent disorder of NO-producing endothelial function.…”
Section: Endothelial Dysfunction and Diabetesmentioning
confidence: 91%